Impaired glucose tolerance in adolescent offspring of diabetic mothers: relationship to fetal hyperinsulinism - Silverman, B.L; Metzger, B.E; Cho, N.H; Loeb, C.A (Diabetes care, 1995)
Objective: To test the hypothesis that long-term postnatal development may be modified by metabolic experiences in utero. Research Design and Methods: We enrolled offspring of women with pregestational diabetes (this included insulin-dependent diabetes mellitus [IDDM] and non-insulin-dependent diabetes mellitus [NIDDM]) and gestational diabetes in a prospective study from 1977 through 1983. Fetal beta-cell function was assessed by measurement of amniotic fluid insulin (AFI) at 32-38 weeks gestation Postnatally, plasma glucose and insulin were measured yearly from 1.5 years of age after fasting and 2 h after 1.75 g/kg oral glucose. Control subjects had a single oral glucose challenge at 10-16 years. Results: In offspring of diabetic mothers, the prevalence of impaired glucose tolerance (IGT) (2-h glucose concentration >7.8 mmol/l) was: 1.2% at <5 years, 5.4% at 5-9 years, and 19.3% at 10-16 years. The 88 offspring of diabetic mothers (12.3 +/- 1.7 years), when compared with 80 control subjects of the same age and pubertal stage, had higher 2-h glucose (6.8 +/- 1.4 vs. 5.7 +/- 0.9 mmol/l, P < 0.001) and insulin (660 +/- 720 vs. 455 +/- 285 pmol/l P < 0.03) concentrations. The 17 subjects with IGT at > 10 years of age (9 boys and 8 girls) include one girl with NIDDM. IGT was not associated with the etiology of the mother's diabetes (gestational versus pregestational) or macrosomia at birth IGT was found in only 3.7% (1 of 27) of adolescents whose AFI was normal (less than or equal to 100 pmol/l) and 33.3% (12 of 36) of those with elevated AFI (P < 0.001). Although most of the children with IGT are obese, AFI and obesity are independently associated with IGT by multiple logistic analysis. Conclusions: In confirmation of our original hypothesis; IGT in the offspring is a long-term complication of maternal diabetes. Excessive insulin secretion in utero, as assessed by AFI concentration, is a strong predictor of IGT in childhood.